Synthesis, Characterization and Biological Activity of Some New 4-Substituted-phenyl-3-chloro-1-{5-[(3, 5-dimethyl-1H-pyrazol-1- yl) methyl]-1, 3, 4-thiadiazol-2-yl} azetidin-2-one - Al-Smaisim, Rafah Fadhil (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2012)
A new series of 3,5-dimethyl-1H-pyrazole derivatives (1-15) incorporated into fused to different nitrogen and sulphur containing heterocyclic were prepared from 3,5-dimethyl-1H-pyrazole when treated with ethylchloroacetate in the present of potassium carbonate to offer Ethyl (3, 5-dimethyl-1H-pyrazol-1-yl) acetate (1). Compound (1) converted to 2-[(3,5-dimethyl -1H-pyrazol -1-yl) acetyl] hydrazinecarbothioamide (2) by reaction with thiosemicarbazide in methanol. Cyclocondensation (2) was reacted with mineral acid H2SO4 to produce 5-[(3, 5- dimethyl-1H-pyrazol-1-yl) methyl]-1, 3, 4-thiadiazol-2-amine (3). Various new Schiff bases (4-9) were synthesized by the condensation of 5-[(3, 5-dimethyl-1H-pyrazol-1- yl) methyl]-1, 3, 4-thiadiazol-2-amine (3) with various aryl aromatic aldehydes.A series of six new 4-substituted-phenyl-3-chloro-1-{5-[(3,5-dimethyl-1H-pyrazol-1- yl)methyl]-1,3,4-thiadiazol-2-yl}azetidin -2-one (10-15) have been synthesized by condensation of various Schiff bases (4-9) with chloroacetyl chloride in presence of triethylamine. The structures of the new compounds (1-15) have been characterized by elemental analysis and spectral data. The newly synthesized compounds (10-15) were screened for their antibacterial activity against four bacterial species. They were found to exhibit good antibacterial activity.